Transverse bunch‐by‐bunch feedback system for time‐resolved experiments at PLS‐II. (8th July 2021) - Lee, Jaeyu; Nakamura, T.; Kobayashi, K.; Kim, D.-T.; Ha, T.; Hahn, G.-R.; Kim, K.-J.; Shin, S.
Abstract : A description of the upgraded bunch‐by‐bunch feedback system for time‐resolved experiments at Pohang Light Source II (PLS‐II) is provided. The project is part of the SPring‐8 and PLS‐II collaboration. Abstract : A description of the upgraded bunch‐by‐bunch feedback system for time‐resolved experiments at Pohang Light Source II (PLS‐II) is provided. The bunch‐by‐bunch feedback system has been upgraded to increase the single‐bunch current in the hybrid fill pattern of the PLS‐II facility. The project is part of the SPring‐8 and PLS‐II collaboration. The main features of the upgrade are to employ a single 500 MHz analog‐to‐digital converter (ADC) instead of the previous four 125 MHz interleaved ADCs for 500 MHz rate, to replace a single‐loop two‐dimensional feedback with two independent one‐dimensional feedback loops, to implement the tune measurement function with a single bunch, and mainly to implement single‐bunch and stretcher control. The realization of a 400 mA hybrid fill pattern including a 10 mA single bunch demonstrates the precision of the upgraded bunch‐by‐bunch feedback system.